School Inspection Practices Evidence from Secondary Schools in Western Uganda - Bagaya, Jerry; Ezati, Betty Akullu; Wafula, Wycliffe Scot; Rasmussen, Palle Damkjær (Journal of Education and Training, 2020)
The study examined inspection practices in secondary schools in Western Uganda. Towards achieving this objective, a Concurrent Triangulation Mixed Methods Design, involving questionnaire survey and interview, with a total of 399 participants in the categories of teachers, head teachers, school inspectors from 36 second ary schools in four districts of Western Uganda, was adopted. Quantitative data to test the resultant hypothesis were analysed using Chi Square Goodness of Fit Test while qualitative data were analysed using Qualitative Content Analysis. The study revealed that inspection practices in secondary schools were perceived as largely ineffective. The study concluded that despite the value attached to school inspection in the theoretical, political, and institutional and policy debates, inspectors continue to think and act according to the traditional notions of school inspection as evidenced by practices hinged on control. The major implication of the study is that understanding the practices before, during and after school inspection will allow policy makers, ins pectors, teachers and headteachers to design better practices and benefit from them. The study also proposes a theoretical model for effective school inspection that requires further research and measurement to determine its validity so that lessons can be learnt that can assist inspectors in the future.
Keywords: Inspection, inspection practices, Secondary schools, Uganda